2002
DOI: 10.1302/0301-620x.84b6.0840873
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of sacral giant-cell tumours by serial arterial embolisation

Abstract: Giant-cell tumours of the sacrum are difficult to treat. Surgery carries a high risk of morbidity, local recurrence and mortality. Radiation is effective in some patients, but has a risk of malignant change. We evaluated the effectiveness of serial arterial embolisation as an alternative to surgery. Five patients with giant-cell tumours of the sacrum which had been primarily treated by serial embolisation were retrospectively reviewed for changes in the size of the tumour. In four the symptoms resolved with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 0 publications
2
32
1
Order By: Relevance
“…54,55 Five-year survival rates as high as 90% have been reported for patients with low-grade tumors, while the corresponding rates for patients with high-grade tumors are 40%-50%. 46,[55][56][57][58][59] We have used image guidance in treating patients with chondrosarcoma to improve our surgical margins while limiting our complications by avoiding excessive bone resection and preserving neurovascular structures. Our intraoperative goal is to obtain at least a 2-cm margin from the tumor seen on intraoperative CT and correlated with MRI.…”
Section: Surgical Pearlsmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 Five-year survival rates as high as 90% have been reported for patients with low-grade tumors, while the corresponding rates for patients with high-grade tumors are 40%-50%. 46,[55][56][57][58][59] We have used image guidance in treating patients with chondrosarcoma to improve our surgical margins while limiting our complications by avoiding excessive bone resection and preserving neurovascular structures. Our intraoperative goal is to obtain at least a 2-cm margin from the tumor seen on intraoperative CT and correlated with MRI.…”
Section: Surgical Pearlsmentioning
confidence: 99%
“…Its ability to halt growth of tumor has been described. [72][73][74] Lackman et al 58 reported on 5 cases of sacral GCT treated solely with recurrent arterial embolization, with 4 demonstrating no growth or recurrence. Intralesional curettage is the mainstay of treatment in long bones and is often combined with local adjuvants such as cryotherapy, peroxide, ethanol, phenol, and bone cement to reduce recurrence.…”
Section: Surgical Pearlsmentioning
confidence: 99%
“…Based on the previous inclusion and exclusion criteria, 44 patients from 9 articles were involved in our systematic review; 1 study showing similar data to another was excluded. Among 9 articles, the publication time varied from 1978 to 2013, comprising 34 females and 10 males, with a mean age of 34.4 AE 13.3 years (median, 31.5 years; range, 15-68 years) 20 . …”
mentioning
confidence: 99%
“…Partial sacrectomy is used for tumors with substantial involvement of the sacrum below the S2 segment because it can usually be resected with wide margins and allows patients to maintain bowel and bladder control without the need for lumbopelvic reconstruction. If complete resection cannot be easily achieved, preoperative or serial arterial embolization [10,15,17,21,24], intralesional curettage [16,20,27], cryosurgery [20,27], or radiation therapy [16,23] are alternatives. However, the best treatment for giant cell tumor of the sacrum is controversial and the role of adjuvant treatments is unclear [23].…”
Section: Introductionmentioning
confidence: 99%